Polylinguality as a condition of preservation of cultural values in a modern society - Tleuzhanova, G.K.; Stanciu, N.; Тuleubayeva, Sh.K. (KSU Publ., 2019)
The article is devoted to multilingualism and its functioning in a modern educational society. The article gives grounds for the urgency of multilingualism concepts connected with bilingualism phenomena and discusses the main directions of their development. Multilingualism and polilingualism are the basis for formulating and defining the concepts of multilingual education. The authors have analyzed such concepts as «bilingualism », «multilingualism», «trilingualism», and «polilingualism». The authors also emphasize subjectlanguage integrated learning as one of the multi-linguistic approaches, providing instruction in two subjects simultaneously and being one of the effective mechanisms for forming the professional competence of a future foreign language teacher. The essence of multilingual education is aimed not only at maintaining and developing cultural diversity, norms and forms of activity based on dialogue and interaction of different cultures, but also at the diversity of world politics and culture.
Көптілділік қазіргі қоғамдағы мəдени құндылықтарды сақтау шарты ретінде
Полилингвальность как условие сохранения культурных ценностей в современном обществе
Keywords: bilingualism; multilinguism; trilingualism; plurilingualism; polyglotism; sociological accent; internationalization; individual; micro and macro communities; polylingual approach; subject-language integrated learning; multilingual education